Experience of developing local universities in a historical urban environment on the example of the University of Amsterdam - Sharonova, O. A.; Antyufeev, A. V. (Sot͡s︡iologii͡a︡ goroda, 2025)
In this article, the authors examine the experience of developing the University Quarter of Amsterdam, which is an example of integrating the educational function into the historical environment and modern urban planning solutions. The authors emphasize the importance of preserving the cultural and historical heritage during the modernization and expansion of university territories, as well as the need to create open, permeable public spaces that promote active interaction between the university and the urban community. Particular attention is paid to approaches to adapting historical buildings to modern functions without losing their authenticity, as well as the development of infrastructure solutions — pedestrian routes, water communications and connecting transport corridors — to improve the accessibility of the territory. The article demonstrates that a harmonious combination of historical identity with innovative urban planning concepts contributes to the formation of a dynamic, sustainable and socially integrated urban environment. The analysis is based on the materials of the strategic master plan “University Quarter”, prepared jointly by the University of Amsterdam, the municipality and the studio of urban design and landscape architecture West8. The article provides cultural and historical experience of the university development, the current state and problem areas, solutions and the university's vision. The experience of the University of Amsterdam serves as a valuable example for the development of strategies for the development of university territories in the historic centers of other cities, focused on the preservation of heritage and active participation of citizens